Evaluasi Keterlibatan Gereja Kristen Nazarene di Pulau Jawa Terhadap Isu Eco-Theology di Era Masyarakat 5.0 - Sapto Sunariyanti; Seri Damarwanti; I Made Priana; Darmanto Darmanto; Roni Gunawan (Angelion, 2021)
Genesis 1:26 and 2:15 state that the Church as an integral part of mankind receives mandate from God to preserve the earth which He created good. The earth which once was good but now is facing a crucial environmental problems, such as nature pollution and global warming; which is caused by human indiscretion in managing the earth; become the impetus for this paper to examine whether the Church has been being eco – theology enough and also to explore the Church’s involvement in maintaining the nature as an environment for every creature.  In order to accomplish the objective of this paper, hence the question of whether the Church is still actively carrying out God’s mandate as the steward and caretaker of the earth, becomes the main issue that will be discussed and answered in this research. The selection of the Church of the Nazarene population was determined on the basis that in the perspective of Missio Dei, and the statute of the Church of the Nazarene, the Church plays a role in carrying out God’s Mission through environmental preservation. Java island is appointed as the population based on facts that Java island is the most densely populated area in Indonesia which is vulnerable to environmental damage. The research was conducted with the biblical study approach on the key verse and undertaking evaluation of the Church’s role through a survey method to measure its involvement in environmental issues with various approaches that are possible to be implemented in 5.0 era. The result of the research is expected to become a turning point for the Church’s involvement to be more effective in overcoming environmental problems around the Church. The recency of the research compared with the previous one lies on the implementation aspect of Missio Dei of the Church of the Nazarene, and its relevance towards the Church’s responsibility in preserving the earth. Kejadian 1:26 dan 2:15 menyatakan bahwa Gereja sebagai bagian integral dari umat manusia mendapat mandat dari Tuhan untuk memelihara bumi yang diciptakanNya baik. Bumi yang semula baik adanya, namun kini menghadapi masalah lingkungan hidup yang krusial, seperti pencemaran alam dan pemanasan global; yang diakibatkan oleh ketidakbijaksanan manusia dalam menata bumi; menjadi pendorong dari paper ini untuk  menelisik apakah Gereja sudah cukup ber eco – theology (berteologi alam) dan juga untuk mengeksplorasi bagaimana keterlibatan Gereja dalam memelihara alam sebagai lingkungan hidup setiap makhluk. Dalam rangka mencapai tujuan paper ini, maka pertanyaan apakah Gereja masih menjalankan mandate Tuhan sebagai pengelola dan pemelihara bumi secara aktif, menjadi issue utama yang akan dibahas dan dijawab dalam penelitian ini. Pemilihan populasi Gereja Kristen Nazarene ditentukan atas dasar bahwa dalam perpektif Missio Dei, dan Tata Dasar Gereja Kristen Nazarene; Gereja berperan menjalankan Misi Allah melalui melestarikan lingkungan hidup. Pulau Jawa ditentukan sebagai populasi dengan dasar fakta bahwa Pulau Jawa merupakan area dengan populasi terpadat di Indonesia yang rentan terhadap kerusakan lingkungan. Penelitian dilakukan dengan pendekatan studi biblika atas nats kunci dan melakukan evaluasi atas peran Gereja melalui metode penelitian survey untuk megukur keterlibatannya dalam issue–issue lingkungan hidup dengan berbagai pendekatan yang memungkinkan untuk diimplementasikan di di era 5.0. Hasil penelitian diharapkan dapat menjadi titik balik keterlibatan Gereja lebih efektif dalam mengatasi masalah lingkungan hidup di sekitar Gereja. Kebaharuan penelitian dibandingkan penelitian sebelumnya terletak pada implementasi aspek Misio Dei Gereja Kristen Nazarene, dan relevansinya terhadap tanggungjawab Gereja dalam memelihara bumi.